PENGGUNAAN MODEL PEMBELAJARAN MATERI STATISTIKA DAN DAMPAKNYA TERHADAP HASIL BELAJAR SISWA - d, dian arleni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
ABSTRACT Arleni, Dian. 2020. Use of Learning Models in Statistics Material and Impact on Student Learning Output. SMP Negeri 58 Surabaya. Keywords: Learning Models, Student Learning Output This study was conducted with the aim to find out the use of Statistics Material learning models and their impact on student learning output at SMP Negeri 58 Surabaya. Data collection methods used by researchers in this study are observation, interviews, and documentation. The data analysis technique used is a descriptive exploratory method which aims to describe and conclude the use of Statistics material learning models and their impact on student learning output. The results of this study can be known: (1) in the use of Statistics Material learning models, student understanding has increased 100% from the previous condition. (2) in the use of the learning models Statistics Material has an impact on student learning patterns, such as: the level of concentration, memory, comprehension, endurance of learning time, and an increase in student understanding, which is seen from the increasing level of student learning outcomes by 94,87%.